Diagnostic Biopsy via In-Office Frozen Sections for Clinical Nonmelanoma Skin Cancer. Issue 2 (February 2021) - Mulvaney, Patrick M.; Piris, Adriano; Besaw, Robert J.; Schmults, Chrysalyne D.
Abstract : BACKGROUND: Treatment of nonmelanoma skin cancer (NMSC) by Mohs surgery has traditionally relied on previous pathologic evaluation of paraffin-embedded tissue. Tissue processing by frozen sections allows for expedited diagnosis and treatment; however, data on its accuracy are limited. OBJECTIVE: To measure the accuracy and outcomes of biopsy via frozen sections for clinical NMSC. METHODS: Biopsies of clinical NMSCs processed via frozen sections with in-office diagnosis rendered by one Mohs surgeon were retrospectively reviewed by one board-certified dermatopathologist. Discordant diagnoses were re-read in blinded fashion by both physicians. If still discordant, final diagnosis was determined by consensus discussion. Inter-rater reliability was calculated using Cohen's kappa statistic. RESULTS: Two hundred ninety-seven lesions from 208 patients were included. Correlation between in-office and final diagnosis was 0.876 indicating "almost perfect" concordance. Sensitivity and specificity of in-office diagnosis for detecting malignancy were 98.1% and 94.4%. Seven cases (2.0%) had a clinically relevant change in final diagnosis, but appropriate treatment had been rendered. Two benign lesions (0.7%) initially diagnosed as malignant underwent excision. CONCLUSION: In-office biopsy via frozen sections is highly accurate in confirming NMSC. This practice may speed diagnosis and treatment thus improving outcomes and patient satisfaction. Abstract : Supplemental Digital Content is Available in the Text.